Concussion knowledge among family physicians in Croatia - Marko Herceg; Linda Lusic Kalcina; Ivo Lusic (Concussion, 2018)
Aim: The objective of this study was to administer and analyze results of a survey targeting knowledge about concussion symptoms, diagnosis, treatment and expected recovery among family medicine sp...